LIFE CYCLE ASSESSMENT PADA SISTEM PENGELOLAAN SAMPAH DI WILAYAH SARBAGITA, BALI - Made Gunamantha (Purifikasi, 2010)
The requirement of reliable and scientific based data with more information has induced requirement of decision making tool for solid waste management. This study used life cycle assessment (LCA) methodology as environmental analysis tool for comparing different scenarios for municipal solid waste management. The scenarios which were considered in this study included: landfilling without energy recovery as a representative of existing solid waste management, landfilling with energy recovery, combination of incineration and anaerobic digestion, combination of gasification and anaerobic digestion, direct incineration, and direct gasification. A case study in SARBAGITA region in the Province of Bali is discussed. One tonne of treated solid waste was defined as a functional unit of the systems studied. The Life Cycle Inventory (LCI) analysis was done by including field and laboratory survey to characterize solid waste in area study and using emission factors which were adopted from literature to estimate environmental burdens for each scenario. The inventory results were classified into impact categories, i.e. global warming, acidification, eutrophication, and photochemical oxidant formation. The indicators of categories were quantified by using the equivalence factors of relevant emissions to determine the potential of environmental impact in each scenario. Results of the study showed that in all of the impact categories, the direct gasification scenario had the best environmental profile. A sensitivity analysis was also conducted to examine changes in outcomes of a variety of organic bio-waste inputs, which had no significant effect on the overall results.